Le massacre d’Ascq 1944 par les SS : rejeux médiatiques contemporains des procédures judiciaires (années 2000-2010) - Jean-Paul Barrière (Criminocorpus)
The article aims to explore the contemporary repercussions of the SS massacre committed in Ascq in 1944: 1/ the use of the latter by Jean-Marie Le Pen and the legal proceedings (2005-2013) he incurred for Holocaust denial; 2/ the role of the victims’ descendants and of the traditional media (print media, TV) in France and Germany in the impossible belated trial of the last SS soldiers who took part in this crime (2013-2019). Even if the attention paid to Le Pen, via his public words on Ascq, is logically less than in France, the German press takes very little time to report on this judicial process, especially in the period of presidential elections and strategic changes in the National Front. The rediscovery of the former SS man and the resumption of proceedings against him, for want of a basis in his past actions, was based on denialist statements that transformed Karl M. into a hero of the extreme right (NPD): the actions of the French victims, the journalistic investigations and the specific German judicial processes were combined in the same time frame. After the death of the accused, attention to the Ascq massacre was reduced to northern France media, while in Germany it faded away at a time when reflections on the memory of the dark years and on the attitude of democracies towards neo-Nazis were gaining ground.